Strengthening Islamic Faith in the Quran Tadarus Program Through WhatsApp Groups - Oktavia, Desrita Afni; Saparudin, Rizal; Ilham, Seprian (Ahlussunnah: Journal of Islamic Education, 2025)
This study was motivated by phenomena occurring in Muslim communities in West Sumatra, such as low interest in reading the Quran, a decline in mosque attendance, and the negative influence of gadget use on Muslim youth. In response to these challenges, a group of community members initiated an online Quran tadarus program through a WhatsApp group. This study aims to describe the implementation of the Quran tadarus program through WhatsApp groups, identify supporting and inhibiting factors, and analyze its effectiveness in strengthening Islamic faith. This study uses a qualitative research method with a case study approach. The data sources consist of primary data from mosque administrators, managers of the Quran tadarus program through WhatsApp groups, and the surrounding community who are involved in or aware of the implementation of the tadarus program. Secondary data consists of screenshots of activity reports and scientific literature that support the research analysis. The results of the study show that the Quran tadarus program through WhatsApp groups is carried out in a planned and systematic manner. This is fully supported by mosque administrators and the community. One of the inhibiting factors is the varying reading abilities of participants in terms of fluency and tajwid. This program is very effective, as evidenced by the growth of the tadarus group from one group to four active groups.